Nasal nitric oxide and its metabolites as potential biomarkers for the diagnosis and follow-up of allergic rhinitis - Özergin Coşkun, Zerrin; Arslan, Selçuk; Değer, Orhan; İmamoğlu, Mehmet (ENT Updates, 2017)
Objective: This study was conducted to investigate nasal nitric oxide (nNO) and its metabolites nasal nitrite-nitrate (nNOx) in patients with allergic rhinitis (AR), the effects of two different drugs (oral antihistamine and intranasal steroid) on nNOx and the presence of a correlation between nNOx and clinical parameters. Methods: Sixty patients with active symptoms of perennial AR and 25 healthy adults as a control group were enrolled. The patients were randomized into two groups. Half of the patients received fexofenadine 1x120 mg/day orally, and the other half received triamcinolone acetonide 1x2 puff/day intranasally for one month. The amount of nNOx in nasal lavage fluid was measured by using a commercially available kit and the photometric endpoint determination method. Results: Pre-treatment levels of NOx in the nasal lavage fluids (1.92± 1.20 mg/l) of patients with AR were found to be significantly higher when compared with nasal lavage fluid NOx levels of healthy adults (1.38±0.78 mg/l) (p=0.04). The post-treatment nNOx level (1.52±0.85 mg/l) was significantly lower when compared with the pre-treatment value (p=0.028). Conclusion: Nasal nitric oxide metabolites were shown to be good biomarkers for AR, and that oral fexofenadine significantly decreased nNOx levels.